TD-DFT, DFT, docking, MD simulations, and concentration-dependent SERS investigations of a bioactive trifluoromethyl derivative having human acetylcholinesterase and butyrylcholinesterase in silver colloids - Al-Otaibi, Jamelah S; Mary, Y Sheena; Mary, Y Shyma; Krátký, Martin; Vinsova, Jarmila; Mahmood, Tariq; Gamberini, Maria Cristina; Rajendran Nair, Deepthi S (Journal of molecular modeling, 2023)
CONTEXT: Various concentrations of (E)-4-methoxy-N'-(2-(trifluoromethyl)benzylidene) benzohydrazide (EMT) adsorbed on colloidal silver nanoparticles were studied using SERS and results were compared to the normal Raman spectrum. DFT calculations were used to validate experimental findings. Theoretically, the structures of the EMT and EMT-Ag6 systems were optimized. The UV-Vis spectral analysis's red shift and lower intensity behavior show that EMT has chemisorbed onto Ag nanoparticles. Charge transfer (CT) from Ag to EMT is highlighted by FMO analysis. The CT interaction in EMT and EMT-Ag6 was further verified by MEP and Mulliken charge analyses. The EMT was adsorbed on Ag nanoparticles with tilted orientation and orientation changes with colloidal concentration, according to SERS spectrum analysis. Docking EMT with 4PQE and 5DYW binding affinities are found to be -9.7 and -8.1 kcal/mol. MD simulations give the competence of 5DYW-EMT and 4PQE-EMT in their intended binding interactions and their ability to establish enduring associations with the protein of interest. METHODS: DFT was used to optimize the molecular structures of EMT and EMT-Ag6 using B3LYP/6-311++G* (LANL2DZ basis set for Ag). A molecular dynamics simulation study was conducted on the 4PQE-EMT and 5DYW-EMT systems using the Desmond software for 100 ns.
Keywords: Benzyohydrazide: Silver cluster; DFT; stříbro; Acetylcholinesterase; Spectrum Analysis, Raman; Silver; Humans; Butyrylcholinesterase; Density Functional Theory; lidé; SERS; acetylcholinesterasa; Metal Nanoparticles; kovové nanočástice; Adsorption; Ramanova spektroskopie; butyrylcholinesterasa; teorie funkcionálu hustoty